Selective-referral and Unobserved Patient Heterogeneity – Bias in the Volume-outcome Relationship - Corinna Hentschker; Roman Mennicken (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
This paper examines the causal effect of the experience of a hospital with treating hip fractures (volume) on treatment outcome for patients. A full sample of administrative data from Germany for the year 2007 is used. We apply an instrumental variable approach to eliminate endogeneity concerns due to reverse causality and unobserved patient heterogeneity. As instruments for case volume we use the number of potential patients and the number of further hospitals in the region around every hospital. Our results indicate that after application of an IV regression of volume on outcome, volume significantly increases quality. – – Dieser Beitrag analysiert den kausalen Effekt zwischen der Zahl der Fälle eines Krankenhauses und der Qualität der Behandlung für Patienten mit einer Hüftfraktur. Es werden administrative Daten aus Deutschland für das Jahr 2007 genutzt. Wir führen eine Instrumentenvariablenschätzung durch, um Endogenitätsprobleme durch umgekehrte Kausalität sowie durch ausgelassene Variablen zu eliminieren. Als Instrumente nutzen wir die Anzahl potenzieller Patienten sowie die Anzahl weiterer Krankenhäuser in der Umgebung von jedem Krankenhausstandort. Unsere Ergebnisse zeigen, dass die Fallzahl einen signifikanten Effekt auf die Behandlungsqualität hat und damit als eine Einflussgröße betrachtet werden kann, die die Qualität erhöht.
Keywords: I11; I12; I18; 330; volume; hospital quality; mortality; instrumental variables